Strategi pembelajaran Pendidikan Agama Islam dan Budi Pekerti dalam implementasi Kurikulum Merdeka di sekolah dasar - Tafsir Efendi; Zurifah Nurdin; Mindani Mindani (Curricula: Journal of Curriculum Development, 2026)
Pendidikan Agama Islam dan Budi Pekerti plays a crucial role in shaping the religious character of elementary school students, particularly in addressing the challenges posed by technological development and social change in the digital era. This study aims to analyze the learning strategies for Pendidikan Agama Islam dan Budi Pekerti in implementing the Kurikulum Merdeka in elementary schools in Ulu Musi District, Empat Lawang Regency, including the supporting and inhibiting factors. This study used a descriptive qualitative approach, employing observation, interviews, and documentation as data collection techniques. The research subjects consisted of principals and Pendidikan Agama Islam dan Budi Pekerti teachers in several elementary schools in Ulu Musi District. The results showed that the learning strategies were implemented through the development of teaching modules, grouping students by learning ability, and using diagnostic, formative, and summative assessments. Supporting factors for implementation include teacher readiness, school support, parental involvement, and the availability of facilities and infrastructure. Meanwhile, inhibiting factors include limited facilities, lack of teacher training, and limited internet access and learning resources. This study shows that the successful implementation of the Kurikulum Merdeka requires collaboration between schools, teachers, parents, and the government.